Knowledge and attitude about human immunodeficiency virus/acquired immunodeficiency syndrome among higher secondary school students of Jaipur city: A cross-sectional study - Pankaj Chaudhary; Jitender Solanki; Om Prakash Yadav; Priyanka Yadav; Preyas Joshi; Mohsin Khan (Wolters Kluwer Medknow Publications, 2016)
Introduction: India is estimated to have the third highest number of human immunodeficiency virus (HIV) infections in the world with about 20.89 lakh people currently living with HIV/acquired immunodeficiency syndrome (AIDS). Inadequate knowledge, negative attitudes, and ignorance among the school students are major hindrances to prevent the spread of HIV. Aim: To assess the knowledge and attitude toward HIV/AIDS among the higher secondary school students of Jaipur city. Materials and Methods: A questionnaire-based cross-sectional study comprising 613 higher secondary school students (male = 390, female = 223) from Jaipur city were included in the study. The city was divided into 4 zones and one school from each zone was selected randomly. A questionnaire assessing the knowledge and attitude toward HIV/AIDS was distributed among the senior school students. Pilot study was done among 50 students to test the validity of the questionnaire. Results: All the students (100%) in our sample knew what is AIDS. About 96.2% of the students knew that AIDS is not a simple disease, the correct knowledge about the modes of transmission of HIV/AIDS was nearly 85.6% and about 94% of students would not leave the school if there was an AIDS student in their class. Eighty-four percent of students believed that students with AIDS should not go to special schools and about 95.8% students believed that HIV individuals must be supported, treated, and helped. Conclusion: The students had satisfactory knowledge about HIV/AIDS and their attitude toward this group of people was good. There is need and opportunity to provide factual and precise knowledge on HIV/AIDS for school students. There should also be a drive to increase education and awareness about HIV/AIDS in educational institutes.